Preparation method and application of coal-based hard carbon negative electrode material
The coal-based hard carbon negative electrode material prepared through hydrothermal reaction and filling treatment solves the problem of poor conductivity of coal-based hard carbon, significantly improves its conductivity and kinetic properties, and improves the performance of secondary batteries.
Patent Information
- Application Number
- CN202510063352.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The conductivity of coal-based hard carbon is poor, which affects its dynamic properties and the performance of secondary batteries.
By mixing the raw coal and graphene slurry for hydrothermal reaction, forming a coal-based aerogel, then filling with large pores and micropores, and finally high-temperature carbonization treatment, a coal-based hard carbon negative electrode material with high conductivity and kinetic properties was prepared.
It significantly improves the conductive properties and kinetic properties of coal-based hard carbon and enhances its application potential in secondary batteries.
Smart Images

Figure CN119911894A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a preparation method and application of a coal-based hard carbon negative electrode material. Background Art
[0002] With the rapid development of modern electronic devices, electric vehicles and energy storage systems, the demand for high-performance batteries is growing. As two mainstream secondary batteries, the performance of lithium-ion batteries and sodium-ion batteries depends largely on electrode materials. The characteristics of negative electrode materials have a crucial impact on key performance indicators such as battery capacity, cycle life, and charge and discharge efficiency. In this demand context, the continuous exploration of new and efficient negative electrode materials has become one of the hot topics in the battery field.
[0003] Although traditional negative electrode materials, such as graphite, meet the basic needs of batteries to a certain extent, they also have some obvious limitations. For example, the theoretical specific capacity of graphite is relatively limited, which makes it difficult to meet the requirements of high energy density batteries. Moreover, during high current charging and discharging, graphite is prone to structural collapse and other problems, resulting in a shortened battery cycle life. These limitations have prompted researchers to look for new negative electrode materials with higher specific capacity and better cycle stability.
[0004] Hard carbon materials have shown great potential in the field of battery negative electrode materials due to their unique structure and properties. Hard carbon has a disordered microstructure, which can provide more active sites, thus facilitating the storage and transport of ions. Compared with traditional graphite materials, hard carbon usually has a higher specific capacity and can maintain good structural stability during the cycle process. Based on these advantages, the preparation and optimization of hard carbon materials have become the focus of research.
[0005] Common hard carbon materials include biomass hard carbon and resin hard carbon. Compared with biomass hard carbon and resin hard carbon, coal-based hard carbon has been less studied. However, its coal raw materials are abundant and stable in source. The prepared hard carbon materials have the characteristics of low cost and high compaction, and are a promising negative electrode material. Therefore, coal-based hard carbon negative electrode materials show high capacity in lithium-ion batteries and sodium-ion batteries, and have high application potential.
[0006] However, for coal-based hard carbon, its "house of cards" and porous structure result in poor electrical conductivity, which seriously affects its kinetics. Its complex internal functional group types and polycyclic aromatic hydrocarbon structure result in a significant lack of electrical conductivity.
[0007] Therefore, it is urgent to design a preparation method for coal-based hard carbon negative electrode materials to solve the problem of poor conductivity of coal-based hard carbon, thereby improving the kinetic properties of coal-based hard carbon and obtaining secondary batteries with excellent performance. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention aims to provide a method for preparing and applying a coal-based hard carbon negative electrode material with high electrical conductivity and kinetic properties.
[0009] One of the purposes of the present invention is to provide a method for preparing a coal-based hard carbon negative electrode material, the preparation method comprising the following steps: First, the raw coal and graphene slurry are mixed, subjected to a hydrothermal reaction, and then subjected to a low-temperature carbonization treatment to obtain a coal-based aerogel; Then, macropore filling and micropore filling are performed in sequence, using a water-soluble resin for macropore filling and a deposition gas for micropore filling; Then, high temperature carbonization treatment is performed to obtain the coal-based hard carbon negative electrode material; Wherein, the raw coal is powdered raw coal.
[0010] Preferably, the graphene slurry comprises graphene oxide slurry, and the concentration of the graphene slurry is 10-50 mg / mL.
[0011] Preferably, the weight ratio of the raw coal to the graphene slurry is (1-5):10.
[0012] Preferably, the preparation method further comprises the step of pulverizing the raw coal to obtain fine powder coal particles, which are then mixed with graphene slurry, and the particle size D50 of the fine powder coal particles is 4-10 μm.
[0013] Preferably, the reaction temperature of the hydrothermal reaction is 150-250° C., and the reaction time is 2-12 h.
[0014] Preferably, the temperature of the low-temperature carbonization treatment is 550-650° C., and the reaction time is 2-5 hours.
[0015] Preferably, the macropore filling method comprises: After the coal-based aerogel and the water-soluble resin are mixed, a macroporous impregnation filling treatment is performed to obtain the impregnated coal-based aerogel.
[0016] Preferably, the concentration of the water-soluble resin is 100-500 g / L.
[0017] Preferably, the weight ratio of the coal-based aerogel to the water-soluble resin is (1-10):100.
[0018] Preferably, the temperature of the macroporous impregnation filling treatment is 100-200° C. and the pressure is 0.1-2 MPa.
[0019] Preferably, the water-soluble resin includes one or more of carboxymethyl cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, polyurethane resin, acrylic resin or alkyd resin.
[0020] Preferably, the method of micropore filling comprises: The impregnated coal-based aerogel is treated with micropore filling by chemical vapor deposition to obtain deposited coal-based aerogel.
[0021] Preferably, the deposition gas comprises methane and / or acetylene.
[0022] Preferably, the flow rate of the deposition gas is 100-500 mL / min.
[0023] Preferably, the temperature of the micropore filling treatment is 650-850° C. and the time is 2-5 hours.
[0024] Preferably, the preparation method further comprises the step of pulverizing the deposited coal-based aerogel, and after the pulverization, a coal-based hard carbon precursor with a particle size D50 of 4-7 μm is obtained.
[0025] Preferably, the temperature of the high-temperature carbonization treatment is 1200-1600° C. and the insulation time is 1-10 h.
[0026] Preferably, the high-temperature carbonization process is carried out in an inert atmosphere.
[0027] A second object of the present invention is to provide an application of the coal-based hard carbon negative electrode material obtained by the preparation method as described above in the preparation of secondary batteries.
[0028] The beneficial effects of the present invention include: In the present invention, the mixture of raw coal and graphene slurry is first subjected to a hydrothermal reaction, and the graphene slurry is formed on the surface of the coal particles during the hydrothermal reaction and wraps the coal particles. On the one hand, it can hinder the agglomeration of coal particles, which is conducive to the uniform dispersion of coal particles; on the other hand, this wrapping effect can improve the contact between coal particles, provide a better path for subsequent electron transmission, and greatly increase the rate of electron transmission between particles; thirdly, the hydrothermal reaction can also promote partial structural adjustment and preliminary carbonization inside the coal particles, laying the foundation for subsequent treatment. Then, a low-temperature carbonization treatment is carried out to remove volatile substances in the material, which is conducive to improving the stability of the material, allowing the material to initially form a carbonized structure, and obtaining a coal-based aerogel with high porosity and low density, which provides a good carrier for subsequent filling treatment.
[0029] Then, the coal-based aerogel was filled with macropores and micropores in turn, effectively filling the pores of the aerogel. Macropore filling is used to fill the larger pores in the coal-based aerogel, which is beneficial to increase the true density and structural stability of the material and reduce the adverse effects of the pores on the material properties; micropore filling can further refine the pore structure of the material, increase the specific surface area and active sites of the material, and improve the material's storage capacity for lithium ions and sodium ions. At the same time, macropore filling and micropore filling are also conducive to the formation of a dense carbon layer structure on the pore surface, further increasing the conductivity of coal-based hard carbon, while improving the true density properties of coal-based hard carbon and improving the overall performance of the material.
[0030] Then, a high-temperature carbonization treatment is carried out to further carbonize and crystallize the material, so that the components are better combined together to form a more uniform and stable structure.
[0031] The coal-based hard carbon negative electrode material prepared based on this method has a "house of cards" structure and has excellent conductivity and kinetic properties, which improves the application potential of the secondary batteries prepared therefrom in passenger cars, energy storage, 3C and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a flow chart of the preparation process of the coal-based hard carbon negative electrode material provided in Example 1. Figure 2 This is the microscopic morphology of the hard carbon product. DETAILED DESCRIPTION
[0033] In the following description, certain specific details are included to provide a comprehensive understanding of each disclosed embodiment. However, one skilled in the relevant art will recognize that the embodiments can be implemented without one or more of these specific details, but with other methods, components, materials, etc.
[0034] Unless otherwise required herein, the words "include" and "comprising" should be interpreted as having an open and inclusive meaning, ie, "including but not limited to".
[0035] References to "one embodiment" or "an embodiment" or "a preferred embodiment" or "certain embodiments" throughout this specification mean that the specific referenced elements, structures or features described in connection with the embodiment are included in at least one embodiment. Therefore, the phrases "in one embodiment" or "in an embodiment" or "in a preferred embodiment" or "in certain embodiments" appearing in different places throughout the specification do not necessarily all refer to the same embodiment. In addition, the specific elements, structures or features may be combined in any appropriate manner in one or more embodiments.
[0036] According to a first aspect of the present invention, a method for preparing a coal-based hard carbon negative electrode material is provided, the preparation method comprising the following steps: First, the raw coal and graphene slurry are mixed, subjected to a hydrothermal reaction, and then subjected to a low-temperature carbonization treatment to obtain a coal-based aerogel; Then, macropore filling and micropore filling are performed in sequence, using a water-soluble resin for macropore filling and a deposition gas for micropore filling; Then, high temperature carbonization treatment is performed to obtain the coal-based hard carbon negative electrode material; Wherein, the raw coal is powdered raw coal. In the present invention, raw coal and graphene slurry are used, and the raw coal is used as a carbon source, so that the prepared negative electrode material has a house of cards structure, and the graphene slurry has high conductivity. Its unique two-dimensional structure and excellent electron transport performance can bring good conductive properties to the final negative electrode material. In the process of hydrothermal reaction, since the graphene slurry has the characteristics of molding under the conditions of hydrothermal reaction, graphene can wrap coal particles. On the one hand, this wrapping structure can limit the agglomeration of coal particles, so that it maintains a small particle size and good dispersibility in subsequent treatment; on the other hand, this wrapping effect can improve the contact between coal particles, provide a better path for subsequent electron transmission, and greatly increase the rate of electron transmission between particles; thirdly, the unique two-dimensional structure of graphene can form a good interface with the raw coal, provide protection and support for coal particles, and is conducive to the formation of structurally stable coal-based aerogels during low-temperature carbonization, so that the coal-based aerogels maintain the characteristics of high porosity and low density.
[0037] In the present invention, since there are a large number of pores in the coal-based aerogel, including large pores and small pores, the presence of these pores easily causes structural instability or even structural collapse in the subsequent processing process. Therefore, the present invention performs macropore filling and micropore filling on the coal-based aerogel, which can effectively fill the pores of the aerogel. By filling the macropores, the overall structure of the coal-based aerogel becomes more stable, preventing the structural collapse of the coal-based aerogel due to external forces or temperature changes during the subsequent processing, which is beneficial to increase the true density and structural stability of the material and reduce the adverse effects of pores on the performance of the material. Micropore filling can further refine the structure of the material, increase the specific surface area and active sites of the material, and improve the storage capacity of the material for lithium ions or sodium ions. At the same time, macropore filling and micropore filling are also beneficial to form a dense carbon layer structure on the surface of the pores, further increasing the conductivity of the coal-based hard carbon, while improving the true density properties of the coal-based hard carbon and improving the overall performance of the material.
[0038] In the present invention, high temperature carbonization treatment is performed to further carbonize and crystallize the material, so that the components are better combined together to form a more uniform and stable structure.
[0039] The coal-based hard carbon negative electrode material prepared based on this method has a "house of cards" structure and has excellent conductivity and kinetic properties, which improves the application potential of the secondary batteries prepared therefrom in passenger cars, energy storage, 3C and other fields.
[0040] In a preferred embodiment of the present invention, the graphene slurry includes graphene oxide slurry.
[0041] In the present invention, the graphene oxide in the graphene oxide slurry is a curved sheet structure, and the sheet contains a large number of oxygen-containing functional groups. The oxygen-containing functional groups on the surface of graphene oxide can form chemical bonding effects such as hydrogen bonds and covalent bonds with the surface of coal particles, as well as physical adsorption effects such as van der Waals forces. Graphene oxide can better wrap the coal particles, form a stable composite structure, and improve the efficiency of electron transmission between particles. During the hydrothermal reaction, the oxygen-containing functional groups of graphene oxide can react with the active sites on the surface of coal particles, promote the interaction between the two, adjust the pore structure, specific surface area, and conductivity of the negative electrode material, and improve the performance stability of the negative electrode material.
[0042] In addition, graphene oxide has good hydrophilicity and can be dispersed more easily in the hydrothermal reaction system, making it easier to mix with coal particles. Uniform mixing is crucial for the preparation of high-performance negative electrode materials, as it ensures that every coal particle can be effectively combined with graphene oxide, making the final material performance more uniform.
[0043] In the subsequent carbonization process, the good dispersion of graphene oxide also helps to form a more uniform carbon structure, improving the conductivity and mechanical properties of the material. Graphene oxide can also promote the transformation of the carbon structure in coal particles into a more ordered graphite structure, improving the conductivity and cycle stability of the material.
[0044] In the present invention, the raw coal includes any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, slightly sticky coal, non-sticky coal, long flame coal or lignite, or a combination of at least two of them.
[0045] In a preferred embodiment of the present invention, the raw coal is long flame coal.
[0046] In the present invention, the long flame coal has lower aromaticity and more branched structures, contains more aliphatic structures and unsaturated bonds, forms abundant active sites, and is more conducive to reacting with other molecules or groups in the process of forming cross-linked structures and hard carbon structures, thereby promoting the formation and development of the structure and forming abundant pore structures and hard carbon with high specific surface area.
[0047] Specifically, the raw coal and graphene slurry are stirred and mixed, and the stirring and mixing rotation speed is 100-500rpm, for example, 100rpm, 150rpm, 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm or 500rpm, or any point value between any two of the above; the stirring and mixing time is 2-5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, or any point value between any two of the above.
[0048] Preferably, the concentration of the graphene slurry is 10-50 mg / mL, for example, it can be 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 40 mg / mL, 45 mg / mL or 50 mg / mL, or a point value between any two of the above.
[0049] Preferably, the solvent of the graphene slurry includes water or a mixture of water and ethanol.
[0050] In the present invention, if the concentration of the graphene slurry is too low, it may lead to incomplete wrapping of the coal particles, and it is difficult for the graphene to be effectively formed with the coal raw material during molding, and it is difficult to form a good conductive network, which greatly reduces the efficiency of electron transmission between particles; if the concentration of the graphene slurry is too high, the dispersion ability of the coal raw material in the graphene becomes poor, and a large number of coal particle agglomerates appear, which will result in the graphene not being able to evenly wrap the coal particles when mixed with the raw coal, and excessive graphene accumulation may appear locally, while other areas have insufficient graphene content, affecting the uniformity and performance stability of the material.
[0051] Preferably, the weight ratio of the raw coal to the graphene slurry is (1-5):10, for example, 1:10, 1.5:10, 2:10, 2.5:10, 3:10, 3.5:10, 4:10, 4.5:10 or 5:10, or a point value between any two of the above.
[0052] In the present invention, if the weight ratio of the raw coal and the graphene slurry is too small, that is, the amount of graphene slurry used is too much, the hard carbon formed is mainly graphene, which affects the initial effect and reversible capacity of the hard carbon, and may also make the structure of the material too loose, which is prone to collapse and other problems in the subsequent processing process, affecting the stability and mechanical properties of the material; in addition, although graphene has high conductivity, excessive graphene may cause the electron transmission path to be too complicated, thereby reducing the electrical conductivity of the material; it may also affect the embedding and extraction of sodium ions and lithium ions in the material, reducing the charge and discharge performance of the battery.
[0053] If the weight ratio of raw coal and graphene slurry is too large, that is, the amount of graphene slurry used is too small, there will be too many coal particles, which will affect the grafting behavior between graphenes and make long flame coal-based aerogel difficult to form. On the one hand, it is easy to lead to a lack of obvious improvement in the electron transmission rate. On the other hand, it is easy to cause defects in the structure of the material, affecting its dynamic properties.
[0054] Preferably, the preparation method also includes the step of pulverizing the raw coal to obtain fine powder coal particles, which are then mixed with the graphene slurry. The particle size D50 of the fine powder coal particles is 4-10μm, for example, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm, and any point value between any two of the above.
[0055] In the present invention, finely powdered coal particles with smaller particle sizes are beneficial to the subsequent mixing with graphene slurry and the progress of the reaction, thereby increasing the contact area and the reaction activity.
[0056] In a preferred embodiment of the present invention, the reaction temperature of the hydrothermal reaction is 150-250°C.
[0057] In the present invention, if the temperature of the hydrothermal reaction is too low, the grafting reaction conditions between the graphene oxides cannot be achieved, resulting in the failure of the long flame coal-based aerogel to be formed; if the temperature of the hydrothermal reaction is too high, the formed long flame coal-based aerogel will be hydrolyzed at high temperature.
[0058] In the present invention, if the temperature of the hydrothermal reaction is too low, the interaction between the raw coal and the graphene slurry is weakened, the encapsulation process becomes slow or even difficult to proceed, it is difficult to form a good composite structure, and the structural reorganization and carbonization process of the coal particles are restricted, which easily leads to an uneven structure of the coal-based aerogel; if the temperature of the hydrothermal reaction is too high, on the one hand, the coal-based aerogel is prone to hydrolysis, which will make the bonding between the graphenes poor, and on the other hand, the reaction is too violent, and it is difficult to accurately control the reaction process, which may lead to uneven structure of the product, local overheating, excessive carbonization and other problems. Too high a temperature may also destroy the structure of the coal particles and the graphene oxide, which easily makes it lose its original performance advantages. Therefore, the reaction temperature of the hydrothermal reaction is 150-250°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, or a point value between any two of the above.
[0059] Preferably, the hydrothermal reaction time is 2-12 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h, or a value between any two of the above.
[0060] In a preferred embodiment of the present invention, the temperature of the low-temperature carbonization treatment is 550-650°C, for example, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C, and any point value between any two of the above.
[0061] In the present invention, low-temperature carbonization can remove some volatile substances, open the pores of the aerogel, and facilitate the subsequent liquid phase impregnation macroporous filling and vapor phase deposition microporous filling. At the same time, low-temperature carbonization can also make the material initially form a carbonized structure, improve the stability of the material, and obtain a coal-based aerogel. If the temperature of the low-temperature carbonization treatment is too low, the carbonization may not be sufficient, the volatile substances in the raw materials cannot be fully removed, and the structure formed at low temperature is relatively loose, the stability of the material cannot be effectively improved, and the coal-based aerogel cannot be smoothly converted into an intermediate product with a preliminary carbonized structure. The structure formed at low temperature is relatively loose, and the pore structure may not be regular enough, and it cannot provide a good foundation for subsequent macroporous filling and microporous filling. If the temperature of the low-temperature carbonization treatment is too high, it may cause excessive carbonization, destroy some beneficial components in the material, collapse the pore structure, and reduce the specific surface area. At the same time, excessive carbonization may also make the material too hard and difficult to carry out subsequent processing.
[0062] Preferably, the reaction time of the low-temperature carbonization treatment is 2-5 h, for example, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, and any value between any two of the above points.
[0063] In a preferred embodiment of the present invention, the macropore filling method comprises: After the coal-based aerogel and the water-soluble resin are mixed, a macroporous impregnation filling treatment is performed to obtain the impregnated coal-based aerogel.
[0064] In the present invention, the purpose of macropore filling is to fill the penetrating macropores formed in the aerogel and increase the true density of the hard carbon formed. The macropores refer to pores with a pore diameter of more than 50 nm.
[0065] In the present invention, the water-soluble resin has good fluidity and wettability, which is beneficial to filling in the macropores. After the resin is solidified in the macropores, it can prevent the aerogel from structural collapse due to external forces or temperature changes during subsequent processing, thereby providing a more uniform and stable basis for micropore filling treatment, so that the subsequent micropore filling process can be carried out more uniformly.
[0066] Preferably, the water-soluble resin includes one or more of carboxymethyl cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, polyurethane resin, acrylic resin or alkyd resin.
[0067] Preferably, the concentration of the water-soluble resin is 100-500 g / L, for example, 100 g / L, 200 g / L, 300 g / L, 400 g / L or 500 g / L, and values between any two of the above points.
[0068] Preferably, the weight ratio of the coal-based aerogel to the water-soluble resin is (1-10):100, for example, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100 or 10:100, and points between any two of the above points.
[0069] In the present invention, if the weight ratio of coal-based aerogel to water-soluble resin is too small, it is easy to cause excessive resin to make the structure of the material too dense and the porosity too much reduced in the subsequent processing process, which may affect the transmission and storage of lithium ions and sodium ions and reduce the electrochemical performance of the material; if the weight ratio of coal-based aerogel to water-soluble resin is too large, the impregnation effect of water-soluble resin is poor, the internal penetration effect of coal-based aerogel is poor, and insufficient filling may occur, making it difficult to effectively fill the macropores of coal-based aerogel. It is impossible to form a good composite structure, which affects the pore structure and electrochemical performance of the material.
[0070] Preferably, the temperature of the macroporous impregnation filling treatment is 100-200°C, for example, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, and values between any two of the above points.
[0071] Preferably, the pressure of the macroporous impregnation filling treatment is 0.1-2 MPa, for example, 0.1 MPa, 0.5 MPa, 1 MPa, 1.5 MPa or 2 MPa, and values between any two of the above points.
[0072] In the present invention, the macroporous impregnation filling treatment is limited to be carried out at a temperature of 100-200°C and a pressure of 0.1-2MPa, which helps to promote the fluidity and wettability of the water-soluble resin, fully wet the pore walls of the aerogel, and help the water-soluble resin enter the interior of the coal-based aerogel, thereby achieving more uniform and sufficient filling.
[0073] In a preferred embodiment of the present invention, the micropore filling method comprises: The impregnated coal-based aerogel is treated with micropore filling by chemical vapor deposition (CVD) to obtain deposited coal-based aerogel.
[0074] In the present invention, the purpose of micropore filling is to fill the pores that cannot be filled by water-soluble resins, forming closed pores to fill active sodium ions. Micropores refer to pores with a pore diameter of ≤2nm.
[0075] In the present invention, by depositing carbon atoms in the micropores, the size of the micropores becomes more uniform and the porosity is reduced. On the one hand, this helps to increase the specific surface area and the number of active sites of the material. On the other hand, the deposited carbon atoms form a continuous carbon network in the micropores, further improving the conductivity of the material. Thirdly, it is also beneficial to form a dense carbon layer structure on the surface of coal-based hard carbon, which not only increases the conductivity of coal-based hard carbon, but also improves its true density properties.
[0076] Preferably, in the chemical vapor deposition method, the deposition gas comprises methane and / or acetylene.
[0077] Preferably, the flow rate of the deposition gas is 100-500 mL / min, for example, 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min or 500 mL / min, and values between any two of the above points.
[0078] Preferably, the temperature of the micropore filling treatment is 650-850°C, for example, 650°C, 700°C, 750°C, 800°C or 850°C, and any point value between the above two points; the time of the micropore treatment is 2-5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, and any point value between the above two points.
[0079] In the present invention, if the temperature of the micropore filling treatment is too low, it is difficult for the deposited gas to fully decompose and form effective filling in the micropores, which will lead to insufficient filling; in addition, the filling structure formed at low temperature may not be stable enough. In subsequent treatment processes, such as high-temperature carbonization treatment, these unstable filling structures may change or be destroyed, affecting the overall performance and stability of the material.
[0080] If the temperature of micropore filling treatment is too high, the reaction of the deposited gas will be too violent, making it difficult to accurately control the reaction process, which may lead to problems such as uneven filling, overfilling or local overheating, which can easily affect the skeleton structure properties of coal-based aerogels and affect the pore structure and performance of the material. Excessive temperature may also affect the interaction between the deposited gas and the aerogel, resulting in instability of the filling structure.
[0081] In a preferred embodiment of the present invention, the preparation method also includes the step of crushing the deposited coal-based aerogel to obtain a coal-based hard carbon precursor with a particle size D50 of 4-7 μm, for example, 4 μm, 5 μm, 6 μm or 7 μm, and point values between any two of the above points.
[0082] In the present invention, after macropore filling and micropore filling treatment, the deposited coal-based aerogel obtained may have a larger size or uneven particle distribution. Through pulverization treatment, it is adjusted to particles with a particle size D50 of 4-7μm, which is more conducive to subsequent high-temperature carbonization treatment, so that the material can be heated and reacted more evenly during the high-temperature treatment process.
[0083] Specifically, the parameters for crushing the deposited coal-based aerogel include: a spiral feed frequency of 20-30 Hz, for example, 20 Hz, 22 Hz, 24 Hz, 26 Hz, 28 Hz or 30 Hz, and any point value between the above two; a classifier frequency of 60-80 Hz, for example, 60 Hz, 65 Hz, 70 Hz, 75 Hz or 80 Hz, and any point value between the above two; an induced draft fan frequency of 40-50 Hz, for example, 40 Hz, 42 Hz, 44 Hz, 46 Hz, 48 Hz or 50 Hz, and any point value between the above two.
[0084] In a preferred embodiment of the present invention, the temperature of the high temperature carbonization treatment is 1200-1600°C, for example, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C, and any point value therebetween.
[0085] Preferably, the holding time of the high temperature carbonization treatment is 1-10 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, and any value between any two of the above.
[0086] Preferably, the high temperature carbonization process is carried out in an inert atmosphere, such as nitrogen or argon.
[0087] Preferably, the heating rate of the high temperature carbonization treatment is 1-10°C / min, for example, 1°C / min, 3°C / min, 5°C / min, 7°C / min or 9°C / min, and any point value between any two of the above.
[0088] In the present invention, a heating rate of 1-10° C. / min is beneficial for uniform heating of the material during the entire heating process, and is beneficial for structural stability and pore adjustment.
[0089] Preferably, the preparation method comprises the following steps: (1) The raw coal is crushed to obtain fine powder particles with a particle size D50 of 4-10 μm, and then the fine powder particles are mixed with a graphene oxide slurry with a concentration of 10-50 mg / mL, and then a hydrothermal reaction is carried out at 150-250°C for 2-12 hours, and then a low-temperature carbonization treatment is carried out at 550-650°C for 2-5 hours to obtain a coal-based aerogel; The weight ratio of the raw coal to the graphene slurry is (1-5):10, the stirring and mixing speed is 100-500 rpm, and the stirring and mixing time is 2-5 hours; (2) placing the coal-based aerogel into an impregnation kettle, adding a water-soluble resin with a concentration of 100-500 g / L, and performing macroporous impregnation filling treatment at 100-200° C. and 0.1-2 MPa to obtain an impregnated coal-based aerogel; then placing the impregnated coal-based aerogel in a CVD device, passing a deposition gas with a flow rate of 100-500 mL / min, and performing a microporous filling treatment at a temperature of 650-850° C. for 2-5 hours to obtain a deposited coal-based aerogel; then pulverizing the deposited coal-based aerogel to obtain a coal-based hard carbon precursor with a particle size D50 of 4-7 μm; The weight ratio of coal-based aerogel to water-soluble resin is (1-10):100, and the specific parameters of the crushing process include: the frequency of the spiral feed is 20-30Hz, the frequency of the classifier is 60-80Hz, and the frequency of the induced draft fan is 40-50Hz; (3) In an inert atmosphere, the temperature is raised to 1200-1600° C. at a heating rate of 1-10° C. / min, and the coal-based hard carbon precursor is subjected to high-temperature carbonization treatment for a holding time of 1-10 h to obtain the coal-based hard carbon negative electrode material.
[0090] According to a second aspect of the present invention, there is provided a use of a coal-based hard carbon negative electrode material obtained by the preparation method described in the first aspect in preparing a secondary battery.
[0091] Preferably, the secondary battery comprises a lithium ion battery or a sodium ion battery.
[0092] Example The present invention is further described in detail below in conjunction with the embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
[0093] In the following examples, unless otherwise specified, all raw materials are commercially available products.
[0094] Example 1 This embodiment provides a method for preparing a coal-based hard carbon negative electrode material. The process flow chart of the preparation process of the coal-based hard carbon negative electrode material is as follows: Figure 1 As shown, the preparation method comprises the following steps: (1) The raw coal is crushed to obtain fine powder particles with a particle size D50 of 7 μm, and then stirred and mixed with a graphene oxide slurry with a concentration of 30 mg / mL, and then subjected to a hydrothermal reaction at 200°C for 7 h, and then subjected to a low-temperature carbonization treatment at 600°C for 3 h to obtain a coal-based aerogel; The raw coal is long flame coal, the solvent of the graphene oxide slurry is water, the weight ratio of the raw coal to the graphene oxide slurry is 3:10, the stirring and mixing speed is 300 rpm, and the stirring and mixing time is 3 hours; (2) placing the coal-based aerogel into an impregnation kettle, adding a water-soluble resin with a concentration of 300 g / L, and performing macroporous impregnation filling treatment at 150° C. and 1 MPa to obtain an impregnated coal-based aerogel; then placing the impregnated coal-based aerogel in a CVD device, introducing methane with a flow rate of 300 mL / min, and performing microporous filling treatment at a temperature of 750° C. for 3 hours to obtain a deposited coal-based aerogel; then pulverizing the deposited coal-based aerogel to obtain a coal-based hard carbon precursor with a particle size D50 of 5 μm; The water-soluble resin used was a carboxymethyl cellulose aqueous solution with a concentration of 300 g / L, the weight ratio of coal-based aerogel to water-soluble resin was 5:100, and the specific parameters of the crushing process included: the spiral feed frequency was 25 Hz, the classifier frequency was 70 Hz, and the induced draft fan frequency was 45 Hz; (3) In an inert atmosphere, the temperature is raised to 1400° C. at a heating rate of 5° C. / min, and the coal-based hard carbon precursor is subjected to a high-temperature carbonization treatment for 5 h to obtain the coal-based hard carbon negative electrode material.
[0095] Example 2 This embodiment provides a method for preparing a coal-based hard carbon negative electrode material, the preparation method comprising the following steps: (1) The raw coal is crushed to obtain fine powder particles with a particle size D50 of 8 μm, which are then stirred and mixed with a graphene oxide slurry with a concentration of 10 mg / mL, and then subjected to a hydrothermal reaction at 150°C for 12 h, and then subjected to a low-temperature carbonization treatment at 550°C for 2 h to obtain a coal-based aerogel; The raw coal is lean coal, the solvent of the graphene oxide slurry is water, the weight ratio of the raw coal to the graphene oxide slurry is 1:10, the stirring and mixing speed is 100 rpm, and the stirring and mixing time is 2 h; (2) placing the coal-based aerogel into an impregnation kettle, adding a water-soluble resin with a concentration of 100 g / L, and performing macroporous impregnation filling treatment at 100° C. and 1 MPa to obtain an impregnated coal-based aerogel; then placing the impregnated coal-based aerogel in a CVD device, introducing methane with a flow rate of 100 mL / min, and performing microporous filling treatment at a temperature of 650° C. for 5 hours to obtain a deposited coal-based aerogel; then pulverizing the deposited coal-based aerogel to obtain a coal-based hard carbon precursor with a particle size D50 of 4 μm; The water-soluble resin used was a carboxymethyl cellulose aqueous solution with a concentration of 100 g / L, the weight ratio of coal-based aerogel to the water-soluble resin was 1:100, and the specific parameters of the crushing process included: the spiral feed frequency was 20 Hz, the classifier frequency was 60 Hz, and the induced draft fan frequency was 40 Hz; (3) In an inert atmosphere, the temperature is raised to 1200° C. at a heating rate of 5° C. / min, and the coal-based hard carbon precursor is subjected to a high-temperature carbonization treatment for 10 h to obtain the coal-based hard carbon negative electrode material.
[0096] Example 3 This embodiment provides a method for preparing a coal-based hard carbon negative electrode material, the preparation method comprising the following steps: (1) The raw coal is crushed to obtain fine powder particles with a particle size D50 of 10 μm, which are then stirred and mixed with a graphene oxide slurry with a concentration of 50 mg / mL, and then subjected to a hydrothermal reaction at 250°C for 2 h, and then subjected to a low-temperature carbonization treatment at 650°C for 5 h to obtain a coal-based aerogel; The raw coal is coking coal, the solvent of the graphene oxide slurry is water, the weight ratio of the raw coal to the graphene oxide slurry is 5:10, the stirring and mixing speed is 500 rpm, and the stirring and mixing time is 5 hours; (2) placing the coal-based aerogel into an impregnation kettle, adding a water-soluble resin with a concentration of 500 g / L, and performing macroporous impregnation filling treatment at 200° C. and 2 MPa to obtain an impregnated coal-based aerogel; then placing the impregnated coal-based aerogel in a CVD device, introducing methane with a flow rate of 500 mL / min, and performing microporous filling treatment at a temperature of 850° C. for 2 h to obtain a deposited coal-based aerogel; then pulverizing the deposited coal-based aerogel to obtain a coal-based hard carbon precursor with a particle size D50 of 7 μm; The water-soluble resin used was a carboxymethyl cellulose aqueous solution with a concentration of 500 g / L, the weight ratio of coal-based aerogel to the water-soluble resin was 10:100, and the specific parameters of the crushing process included: the spiral feed frequency was 30 Hz, the classifier frequency was 80 Hz, and the induced draft fan frequency was 50 Hz; (3) In an inert atmosphere, the temperature is raised to 1600° C. at a heating rate of 5° C. / min, and the coal-based hard carbon precursor is subjected to a high-temperature carbonization treatment for 1 h to obtain the coal-based hard carbon negative electrode material.
[0097] Example 4 In this embodiment, the concentration of the graphene oxide slurry is 5 mg / mL.
[0098] The rest is the same as in Example 1.
[0099] Example 5 In this embodiment, the concentration of the graphene oxide slurry is 55 mg / mL.
[0100] The rest is the same as in Example 1.
[0101] Example 6 In this embodiment, the concentration of the graphene oxide slurry is 10 mg / mL.
[0102] The rest is the same as in Example 1.
[0103] Example 7 In this embodiment, the concentration of the graphene oxide slurry is 50 mg / mL.
[0104] The rest is the same as in Example 1.
[0105] Example 8 In this embodiment, the weight ratio of raw coal to graphene oxide slurry is 1:15.
[0106] The rest is the same as in Example 1.
[0107] Example 9 In this embodiment, the weight ratio of raw coal to graphene oxide slurry is 6:10.
[0108] The rest is the same as in Example 1.
[0109] Example 10 In this embodiment, the weight ratio of raw coal to graphene oxide slurry is 1:10.
[0110] The rest is the same as in Example 1.
[0111] Embodiment 11 In this embodiment, the weight ratio of raw coal to graphene oxide slurry is 5:10.
[0112] The rest is the same as in Example 1.
[0113] Example 12 In this embodiment, the temperature of the hydrothermal reaction is 100°C.
[0114] The rest is the same as in Example 1.
[0115] Embodiment 13 In this embodiment, the temperature of the hydrothermal reaction is 300°C.
[0116] The rest is the same as in Example 1.
[0117] Embodiment 14 In this embodiment, the temperature of the hydrothermal reaction is 150°C.
[0118] The rest is the same as in Example 1.
[0119] Embodiment 15 In this embodiment, the temperature of the hydrothermal reaction is 250°C.
[0120] The rest is the same as in Example 1.
[0121] Example 16 In this embodiment, the weight ratio of the coal-based aerogel to the water-soluble resin is 0.5:100.
[0122] The rest is the same as in Example 1.
[0123] Embodiment 17 In this embodiment, the weight ratio of the coal-based aerogel to the water-soluble resin is 15:100.
[0124] The rest is the same as in Example 1.
[0125] Embodiment 18 In this embodiment, the weight ratio of the coal-based aerogel to the water-soluble resin is 1:100.
[0126] The rest is the same as in Example 1.
[0127] Embodiment 19 In this embodiment, the weight ratio of the coal-based aerogel to the water-soluble resin is 10:100.
[0128] The rest is the same as in Example 1.
[0129] Embodiment 20 In this embodiment, the temperature of the micropore filling process is 600°C.
[0130] The rest is the same as in Example 1.
[0131] Embodiment 21 In this embodiment, the temperature of the micropore filling process is 900°C.
[0132] The rest is the same as in Example 1.
[0133] Embodiment 22 In this embodiment, the temperature of the micropore filling process is 650°C.
[0134] The rest is the same as in Example 1.
[0135] Embodiment 23 In this embodiment, the temperature of the micropore filling process is 800°C.
[0136] The rest is the same as in Example 1.
[0137] Embodiment 24 In this embodiment, the graphene slurry is non-oxidized graphene slurry.
[0138] The rest is the same as in Example 1.
[0139] Comparative Example 1 The difference between this comparative example and Example 1 is that the graphene oxide slurry is replaced by graphene oxide powder.
[0140] The rest is the same as in Example 1.
[0141] Comparative Example 2 The difference between this comparative example and Example 1 is that the macropore filling step is not performed.
[0142] The rest is the same as in Example 1.
[0143] Comparative Example 3 The difference between this comparative example and Example 1 is that the micropore filling step is not performed.
[0144] The rest is the same as in Example 1.
[0145] Performance Testing First, the conductivity of the coal-based hard carbon negative electrode materials provided in the above embodiments and comparative examples is tested; the conductivity test is conducted on the powder material formed by hard carbon, and the test method is as follows: first, a uniformly dried powder sample and a calibrated powder resistivity tester are prepared. The powder is placed in a container, the container is filled, and the test circuit is connected, and the pressure parameter is set to 30MPa and the step length is 2MPa for testing.
[0146] Then, the coal-based hard carbon negative electrode material is made into a negative electrode sheet, and the preparation method of the negative electrode sheet includes: mixing the prepared hard carbon, conductive carbon black (Super P), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) according to a formula ratio of 91:2:2:5 for slurry. The prepared slurry is scraped on the carbon-coated copper foil, and then transferred to a 65°C forced air drying oven until the electrode sheet is dry (about 1-2 h), and then transferred to a vacuum drying oven for 12 h to obtain a negative electrode sheet.
[0147] Then, the negative electrode sheet is assembled with the positive electrode sodium sheet, the GF / D glass fiber separator and 1 mol / L NaClO4 electrolyte to obtain a sodium ion button battery.
[0148] The electrochemical performance test of the above sodium ion button battery is carried out: (1) Dynamic performance test The kinetic performance of the sodium ion button cell was tested under the following test conditions: voltage range 0-2 V, kinetic properties were obtained under current density 10C charge / 1C discharge.
[0149] (2) Reversible capacity and initial performance test In the voltage range of 0-2 V, at a current density of 30 mA·g −1 Charge and discharge tests were carried out under the conditions to obtain the discharge reversible capacity and first efficiency.
[0150] The test results are shown in Table 1.
[0151] Table 1 Test results of Examples 1-24 and Comparative Examples 1-3
[0152] analyze: As can be seen from Table 1, the present invention utilizes the characteristics of highly conductive graphene slurry formed under hydrothermal reaction conditions to wrap coal particles during the forming process, greatly improving the efficiency of electron transmission between particles; and, the pores of the aerogel are effectively filled by macropore filling and micropore filling methods, while forming a dense carbon layer structure on the surface of coal-based hard carbon, further increasing the conductivity of the coal-based hard carbon, and improving the true density properties of the coal-based hard carbon. The coal-based hard carbon negative electrode material prepared based on this method has excellent electrical conductivity and kinetic properties, which improves the application potential of the secondary battery prepared therefrom in the fields of passenger cars, energy storage, 3C, etc. The coal-based hard carbon negative electrode material prepared based on the preparation method provided by the present invention exhibits excellent electrical conductivity and kinetic properties.
[0153] It can be seen from Example 1 and Examples 4-7 that if the concentration of graphene oxide slurry is too low, the long flame coal-based aerogel formation effect is poor, resulting in loose bonding between graphene oxide and flame coal, causing its kinetic properties and electrical conductivity properties to decrease; if the concentration of graphene oxide slurry is too high, the dispersion of raw coal particles between graphene is insufficient, and long flame coal particles agglomerate, affecting the kinetic properties of hard carbon.
[0154] It can be seen from Example 1 and Examples 8-11 that if the weight ratio of raw coal and graphene slurry is too small, that is, the amount of graphene slurry used is too much, the hard carbon formed will have a higher reaction in conductivity, but the slow ion transport of long flame coal-based hard carbon will cause the hard carbon to have poor kinetic properties; if the weight ratio of raw coal and graphene slurry is too large, that is, the amount of graphene slurry used is too small, the long flame coal-based aerogel will be difficult to form, and at the same time, the long flame coal particles will affect the conductivity of graphene, resulting in poor electrical conductivity and deteriorating kinetic properties.
[0155] It can be seen from Examples 1 and 12-15 that if the temperature of the hydrothermal reaction is too low, the graphene oxide is not tightly bonded to the raw coal particles, the coal-based aerogel structure is uneven, and the kinetic properties are poor; if the temperature of the hydrothermal reaction is too high, it is easy to cause the long flame coal-based aerogel to hydrolyze, resulting in poor bonding between graphenes, the reaction is too violent, and it may also cause the product structure to be uneven and the conductivity to deteriorate.
[0156] It can be seen from Example 1 and Examples 16-19 that if the weight ratio of long flame coal-based aerogel and water-soluble resin is too small, a large amount of water-soluble resin will make the structure of the material too dense, the porosity will be reduced too much, and it will be difficult for subsequent CVD deposition to enter the interior of the impregnated aerogel, affecting the conductivity of the hard carbon and thus reducing the kinetics; if the weight ratio of long flame coal-based aerogel and water-soluble resin is too large, the water-soluble resin will not be able to be impregnated into the interior of the coal-based aerogel, resulting in a decrease in the capacity, kinetics and conductivity of the hard carbon.
[0157] It can be seen from Example 1 and Examples 20-23 that if the temperature of the micropore filling treatment is too low, it will be difficult for the deposited gas to fully decompose and form effective filling in the micropores, which will lead to insufficient filling and cause some pores to be unable to close, thereby causing the conductivity and kinetic properties of the hard carbon to decrease; if the temperature of the micropore filling treatment is too high, the skeleton structure will change, the micropore filling effect will be poor, and its conductivity and kinetic properties will be affected.
[0158] It can be seen from Example 1 and Comparative Example 1 that if the graphene oxide slurry is replaced with graphene oxide powder, the long flame coal-based aerogel cannot be formed, and the long flame coal particles are separated from the graphene, resulting in poor first effect and reversible capacity of the hard carbon, and decreased conductivity and kinetic properties.
[0159] It can be seen from Example 1 and Comparative Example 2 that if the macropore filling step is not performed, a large number of macropores will be generated. The presence of macropores causes slow electron transport and affects the kinetic properties of hard carbon.
[0160] It can be seen from Example 1 and Comparative Example 3 that if the micropore filling step is not performed, a large number of micropores will cause the reversible capacity and first efficiency of the hard carbon to decrease, while affecting the transmission of electrons, the conductivity will deteriorate, and the kinetic properties will decrease.
[0161] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a coal-based hard carbon negative electrode material, characterized in that: The preparation method The following steps are involved: First, the raw coal and graphene slurry are mixed, subjected to a hydrothermal reaction, and then subjected to a low-temperature carbonization treatment to obtain a coal-based aerogel; Then, macropore filling and micropore filling are performed in sequence, using a water-soluble resin for macropore filling and a deposition gas for micropore filling; Then, high temperature carbonization treatment is performed to obtain the coal-based hard carbon negative electrode material; Wherein, the raw coal is powdered raw coal.
2. The preparation method according to claim 1, characterized in that The graphene slurry includes graphene oxide slurry, and the concentration of the graphene slurry is 10-50 mg / mL; The weight ratio of the raw coal to the graphene slurry is (1-5):10; The preparation method also includes the step of pulverizing the raw coal to obtain fine powder coal particles, which are then mixed with graphene slurry. The particle size D50 of the fine powder coal particles is 4-10 μm.
3. The preparation method according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction is 150-250° C., and the reaction time is 2-12 hours.
4. The preparation method according to claim 1, characterized in that: The temperature of the low-temperature carbonization treatment is 550-650° C., and the reaction time is 2-5 hours.
5. The preparation method according to claim 1, characterized in that: The macropore filling method comprises: After the coal-based aerogel and the water-soluble resin are mixed, a macroporous impregnation filling treatment is performed to obtain an impregnated coal-based aerogel; The concentration of the water-soluble resin is 100-500 g / L; The weight ratio of the coal-based aerogel to the water-soluble resin is (1-10):100; The temperature of the macroporous impregnation filling treatment is 100-200° C. and the pressure is 0.1-2 MPa.
6. The preparation method according to claim 1, characterized in that: The water-soluble resin includes one or more of carboxymethyl cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, polyurethane resin, acrylic resin or alkyd resin.
7. The preparation method according to claim 5, characterized in that: Methods for micropore filling include: The impregnated coal-based aerogel is treated with micropore filling by chemical vapor deposition to obtain deposited coal-based aerogel; The deposition gas includes methane and / or acetylene; The flow rate of the deposition gas is 100-500 mL / min; The temperature of the micropore filling treatment is 650-850°C and the time is 2-5h.
8. The preparation method according to claim 7, characterized in that: The preparation method further comprises the step of pulverizing the deposited coal-based aerogel, and after the pulverization, a coal-based hard carbon precursor with a particle size D50 of 4-7 μm is obtained.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The temperature of the high temperature carbonization treatment is 1200-1600°C and the insulation time is 1-10h; The high-temperature carbonization process is carried out in an inert atmosphere.
10. Use of the coal-based hard carbon negative electrode material obtained by the preparation method according to any one of claims 1 to 9 in the preparation of secondary batteries.
Citation Information
Patent Citations
Coal-based hard carbon negative electrode material of sodium ion battery, preparation method and application thereof
CN113381013A
Negative electrode material, preparation method thereof and battery
CN114789998A
Boron-doped hard carbon negative electrode material and preparation method and application thereof
CN118754103A
P and N co-doped high-compaction coal-based soft / hard carbon negative electrode material and preparation method thereof
CN118771350A
Negative Active Material For Lithium Secondary Battery, Preparing Method For The Same And Lithium Secondary Battery Including The Same
US20210384491A1
Cited By
Industrial production method of coal-based hard carbon precursor
CN122102121A